'To Defeat the Enemy Was Less a Problem Than the Laziness and Indolence of Our Own Commanders … '. Issue 4 (1st October 2016) - Zamulin, Valerii Nikolaevich
ABSTRACT: The most important component of any fighting army's success is its established rear services. Unfortunately, as recently disclosed documents in the Russian Federation's Central Archive of the Ministry of Defense [ TsAMO RF] bear witness, in the spring of 1943 during the preparation for the battle of Kursk, which became a fundamental turning point in the Great Patriotic War, the supply services of the Voronezh Front that was holding the southern shoulder of the Kursk salient were working poorly and seriously affected both the level of combat readiness and the morale of its personnel.